Factors influencing lymph node skip metastasis in colorectal cancer: a retrospective study. Issue 7 (30th November 2017) - Bao, Feng; Deng, Zhi‐gang; Wang, Dong; Xian‐yu, Jian‐bo; Li, Guo‐qiang; Xiang, Chun‐hua; Xiang, Rong‐chao; Zhi, Xing
Abstract : Background: The risk factors for lymph node skip metastasis (LNSM) have not been thoroughly clarified in patients with advanced colorectal cancer (CRC). This study aimed to identify the risk factors for LNSM in CRC patients who underwent laparoscopic radical resection with D3 lymphadenectomy. Methods: This retrospective cohort study included a total of 167 consecutive patients who underwent laparoscopic radical resection with D3 lymphadenectomy for CRC between April 2005 and June 2017. The patients were sorted into the LNSM‐positive (skip+ group) and LNSM‐negative (skip− group) groups. Logistic regression was used to identify the risk factors for LNSM. Results: Compared with the skip− group, the frequency of tumour size <5 cm, pT1‐2 stage, and pN1 stage were significantly higher in the skip+ group (tumour size <5 cm: 68.8 versus 46.7%, P = 0.025; pT1‐2 stage: 18.8 versus 4.4%, P = 0.012; pN1 stage: 78.1 versus 57.0%, P = 0.028), respectively. Multivariate logistic regression analysis revealed that pT1‐2 stage (odds ratio (OR) = 4.3, 95% confidence interval (CI): 1.1–16.6, P = 0.034) and pN1 stage (OR = 2.6, 95% CI: 1.1–6.8, P = 0.047) were independent risk factors for LNSM. Conclusions: pT1‐2 stage and pN1 stage are significantly associated with LNSM. Radical D3 lymphadenectomy should remain standard practice for CRC.